User Generated Branding Integrating User Generated Content into Brand Management - Arnhold, Ulrike. (Gabler, 2010)
What is the value of user generated content in branding? Do social media activities such as brand communities and blogs rather harm or strengthen the brand? Ulrike Arnhold investigates these burning questions, introducing the concept of user generated branding. From a brand management perspective she analyses the impact of interactive marketing programmes in Web 2.0, evaluating user generated content as a tool of the brand communication mix. Her book provides not only a comprehensive empiric analysis but also managerial implications. Thus, this pioneer study will help both scholars and practitioners to gain a thorough understanding of the roots, strategies and applications of user generated content in branding.